¿Cómo evaluar los aprendizajes en matemáticas? - Trelles Zambrano, César Augusto (2017)
This present paper makes a theoretical approach which involves the learning evaluation, analyzes the stages of its procedure as well as the functions and the types of assessment in all the educational process. Additionally, it has taken into consideration the series of changes in the curriculum in recent years and has prepared a proposal of different assessment techniques with their corresponding instruments. These ones could be applied to assess the learning in Mathematics.